SISTEM BUCKET SEBAGAI ALTERNATIF SIMULASI PERTUMBUHAN KOTA DENGAN MODEL BERBASIS AGEN - I Made Indradjaja M Brunner (JURNAL SPEKTRAN, 2017)
Urbanization is a common issue faced by many authorities. Urban population is steadily growing which requires more land for housing and other activities. Predicting urban growth pattern has been challenging efforts for planners. Many models have been developed by various researchers and practitioners to give a glimpse of possible future lookout of the city. This paper attempts to explain the basic of Bucket model, where new inhabitants will fill the more developed urban areas then spill over to less developed urban area and finally to rural areas bordering urban regions. This model is using a grid map as patches in the Agent Based Model (ABM). Each grid cell is filled with land use, population density, and other data to show its advantages compared to others. New inhabitants as the agent can move freely among the grid cells until an appropriate cell is found. Restrictions should be introduced to for each cell to limit the growth. This paper shows the initial idea of an urban growth simulation using ABM. Keywords: Urban Growth Model; Agent Based Model; Urbanization; Grid Map; Geographic Information System